2016
DOI: 10.4049/jimmunol.1502353
|View full text |Cite
|
Sign up to set email alerts
|

IgA Complexes in Plasma and Synovial Fluid of Patients with Rheumatoid Arthritis Induce Neutrophil Extracellular Traps via FcαRI

Abstract: Autoantibodies, including rheumatoid factor (RF), are an important characteristic of rheumatoid arthritis (RA). Interestingly, several studies reported a correlation between the presence of IgA autoantibodies and worse disease course. We demonstrated previously that triggering the IgA Fc receptor (FcαRI) on neutrophils results in neutrophil recruitment and the release of neutrophil extracellular traps (NETs). Because this can lead to tissue damage, we investigated whether IgA immune complexes in plasma and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 48 publications
(48 reference statements)
8
73
0
2
Order By: Relevance
“…The elevated levels of circulating NETs observed in RA could be due to either increased formation of NETs and/or decreased clearance of NETs. Consistent with the first hypothesis, prior findings have demonstrated increased capacity of RA neutrophils to undergo NETosis (9,16), with RA-associated autoantibodies and inflammatory cytokines driving NET formation (9,43). Similarly, we found that RA patients had circulating factors (e.g., immune complexes) promoting neutrophil activation ex vivo.…”
Section: Discussionsupporting
confidence: 91%
“…The elevated levels of circulating NETs observed in RA could be due to either increased formation of NETs and/or decreased clearance of NETs. Consistent with the first hypothesis, prior findings have demonstrated increased capacity of RA neutrophils to undergo NETosis (9,16), with RA-associated autoantibodies and inflammatory cytokines driving NET formation (9,43). Similarly, we found that RA patients had circulating factors (e.g., immune complexes) promoting neutrophil activation ex vivo.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that there is not a general association between autoantibodies and NETs in the sputum. Of interest, these findings are consistent with those in prior studies that demonstrated a strong association of IgA-RF with NET formation, whereas IgG-RF was weakly associated, and IgM-RF was not associated, with NET formation (32).…”
Section: Correlations Of Sputum Net Levels and Rf Levelssupporting
confidence: 91%
“…DEMORUELLE ET AL 2A/a-2 1-20 cyclic , and fibrinogen A [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . Moreover, there was no significant difference in age, sex, race, frequency of SE positivity, or smoking history between the 24 atrisk subjects who underwent NET testing and the 17 who did not (data not shown).…”
mentioning
confidence: 99%
“…Hence, relatively higher levels of IgA‐ACPA are seen in pre‐ and recent‐onset RA patients than IgG ACPA, and may be predictive of RA development and severity. Of note, Aleyd, Al, Tuk, van der Laken, and van Egmond (2016) demonstrated that IgA complexes in the plasma and synovial fluid of patients with RA induce neutrophil extracellular traps via FcaRI, indicating that IgA autoantibodies may play a role in hypercitrullination, induced by NETs.…”
Section: Discussionmentioning
confidence: 99%